EXPLORING THE ROLE OF MIDDLE LEADERS IN MANAGING EMOTIONAL AND PHYSICAL HEALTH IN GAUTENG PROVINCE: A CASE OF MIDDLE SCHOOLS - Mpipo Zipporah Sedio; Vimbi Petrus Mahlangu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This case study explores the role of middle leaders in managing their emotional and physical health in middle schools of Gauteng Province, South Africa. Schools from grades 3 to 6 were purposively selected, and 13 middle managers, including 11 females and 2 males, were interviewed. The study highlights the challenges middle leaders face, such as increased workloads, stress, and maintaining work-life balance, and how these factors impact their overall health. Findings suggest that effective emotional and physical health, increased workload, lack of recognition and support, resources constraints and overcrowded classrooms as well as lack of emotional support affect the well-being of middle managers in schools. The study also provides insights into strategies middle leaders adopt to cope with these challenges, emphasizing the need for institutional support in promoting well-being among school leaders.